Production of Pleurotus ostreatus using corn husks and legumes - Quintana Zamora, Jorge Gustavo (2022)
Pleurotus ostreatus, is an edible mushroom that isproduced in a wide variety of agricultural residues andagro-industrial, due to its great capacity to colonize anddegrade lignocellulosic substrates. The objective of this work was to evaluate the kinetics of radial growth, to obtain of mycelium and the production of Pleurotus ostreatus in the state fresh, using for its growth husk of cob of sweet corn, legume shell (peas, beans and broad beans. In the kinetics of radial growth, which was obtaining of mycelium the one that showed the best behavior in the growth of Pleurotus ostreatus was the culture medium Potato dextrose agar plus the inclusion of pea shell (Pisum sativum) 74 mm at 168 hours of growth, while the best harvest yield of Pleurotus ostreatus was thebean shell (Vicia faba) 151.40 g of Pleurotus ostreatus,per kilogram of substrate in the first harvest. With theseresults, there is an alternative to use the residues ofvegetables that are generated in the central market of the canton Quevedo, Los Ríos Province, Ecuador, in obtainingof a food and reduce the contamination that residuesgenerate in the environment.